2017
DOI: 10.1126/science.aaf4778
|View full text |Cite
|
Sign up to set email alerts
|

Control of meiotic pairing and recombination by chromosomally tethered 26 S proteasome

Abstract: During meiosis, paired homologous chromosomes (homologues) become linked via the synaptonemal complex (SC) and crossovers. Crossovers mediate homologue segregation and arise from self-inflicted double-strand breaks (DSBs). Here, we identify functions in homologue juxtaposition and crossing over of the proteasome, the multi-subunit protease that degrades proteins in the nucleus and cytoplasm. Without proteasome function, homologues fail to pair and instead remain associated with non-homologous chromosomes. Whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
101
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(117 citation statements)
references
References 42 publications
13
101
0
Order By: Relevance
“…Therefore, it is clear that MOF and ZYGO1 play distinct roles during meiosis in rice. Interestingly, recent studies reported that chromosomally tethered proteasomes promote pairing and recombination in mouse, budding yeast, and C. elegans, suggesting that the meiotic programmed degradation event is highly conserved among species (Ahuja et al, 2017;Rao et al, 2017). We also found that ZYGO1 shows limited sequence similarity to FBL12 in mouse.…”
Section: Zygo1 Promotes Bouquet Formation Within An Scf Complexmentioning
confidence: 49%
“…Therefore, it is clear that MOF and ZYGO1 play distinct roles during meiosis in rice. Interestingly, recent studies reported that chromosomally tethered proteasomes promote pairing and recombination in mouse, budding yeast, and C. elegans, suggesting that the meiotic programmed degradation event is highly conserved among species (Ahuja et al, 2017;Rao et al, 2017). We also found that ZYGO1 shows limited sequence similarity to FBL12 in mouse.…”
Section: Zygo1 Promotes Bouquet Formation Within An Scf Complexmentioning
confidence: 49%
“…Alternatively, the binding and release of additional proteins to the SC could also function in this manner. For example, the recent discovery that the proteasome can be associated with synapsed chromosomes [41] provides an attractive model for SC destabilization. We envision two models to explain how desynapsis can be achieved.…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, every chromosome pair obtains many recombination sites but generally yields only one to two crossover sites (Kauppi et al, 2004). Designations of which recombination sites become crossovers involve antagonistic roles between ubiquitin E3 ligase HEI10 and SUMO E3 ligase RNF212 (Reynolds et al, 2013;Qiao et al, 2014;Rao et al, 2017;Ahuja et al, 2017). It is possible that the SMC5/6 complex is a substrate of HEI10 and RNF212.…”
Section: Smc5/6 Localization Pattern Implicates Multiple Functions Dumentioning
confidence: 99%